(Not) all roads lead to Rome : interdisciplinary approaches to mobility in the ancient world - Devesa, Arnau Lario,; Jiménez, Joan Campmany,; Pàllas, Marc Marzo,; Samaniego, Oriol Morillas, (Access archaeology., 2023)
This work considers mobility in Antiquity in its broadest sense from a multidisciplinary perspective. Although mobility is always present in studies of exchange and cultural diffusion, here it is discussed as a key feature of societies, inherent to their functioning and where cultural, social and economic processes meet.